1986
DOI: 10.1007/bf01870218
|View full text |Cite
|
Sign up to set email alerts
|

Polycation inhibition of exocytosis from sea urchin egg cortex

Abstract: The Ca2+-stimulated release of vesicle contents from cortical fragments prepared from sea urchin eggs is an in vitro model for exocytosis. Cortical fragments have been isolated either in suspension (cell surface complex, CSC preparation), or attached to polycation-coated surfaces (cortical lawn, CL preparation). CL, but not CSC, have been reported to undergo a rapid "aging" process whereby they fail to respond to micromolar free Ca2+. Since, in principle, the only difference between the two preparations is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Using the random model, we can rationalize much of the calcium-dependent exocytotic behavior observed in this preparation. These include (a) the sigmoidal dependence of survival on pCa due to the existence of submaximal responses (4, 60); (b) the increase in fusion rate with increase in [Ca2+]i (10,54); (c) the discrepancy between the calcium concentration required for maximal extents and rates (61); (d) shifting of the calcium activation curve with inhibitors of exocytosis (23,34,58); and (e) aging (45,61), where a progressive decrease in calcium sensitivity is observed with time in the isolated planar cortex. The random model succeeds in describing all of these behaviors in the sea urchin with the simple hypothesis that an increase in [Ca2+]i corresponds to an increase in the average number (<n>) and perhaps the efficacy (p) of active fusion complexes at docking sites.…”
Section: The Random Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the random model, we can rationalize much of the calcium-dependent exocytotic behavior observed in this preparation. These include (a) the sigmoidal dependence of survival on pCa due to the existence of submaximal responses (4, 60); (b) the increase in fusion rate with increase in [Ca2+]i (10,54); (c) the discrepancy between the calcium concentration required for maximal extents and rates (61); (d) shifting of the calcium activation curve with inhibitors of exocytosis (23,34,58); and (e) aging (45,61), where a progressive decrease in calcium sensitivity is observed with time in the isolated planar cortex. The random model succeeds in describing all of these behaviors in the sea urchin with the simple hypothesis that an increase in [Ca2+]i corresponds to an increase in the average number (<n>) and perhaps the efficacy (p) of active fusion complexes at docking sites.…”
Section: The Random Modelmentioning
confidence: 99%
“…By invoking schemes involving a single preassembled fusion complex at a docking site, it may be possible to explain some of the individual calcium-dependent behaviors associated with exocytosis. First, it is known that calcium increases the rate of fusion (10,54) and NEM decreases the fusion rate (45). By invoking an intrinsic, time-dependent inactivation process, one can explain both submaximal extents of fusion and the shift in calcium dose-response observed with NEM treatment.…”
Section: Alternative Hypothesesmentioning
confidence: 99%
“…The bottom of the slide chamber and the top of the coverslip were carefully cleaned with a cotton tipped applicator that had been dipped in water to remove any spots of crystallized salt (from buffer evaporation) that may have accumulated on these surfaces. Scattered light was quantitated with a photodiode apparatus (Crabb & Jackson, 1986) and displayed on a potentiometric chart recorder. With our apparatus, the spot from which CV binding is recorded has an area of 98,000 p,m 2 (equivalent to approximately 22 egg PM fragments with an average diameter of 75/zm).…”
Section: Binding Assaymentioning
confidence: 99%
“…Stimulation of brain triglyceride lipase (Le Petit et al, 1986), as well as of a protein (casein) kinase (Leiderman et al, 1985) have been reported. Polylysine, like neomycin, inhibits Ca2+-induced exocytosis of the sea urchin egg cortex (Crabb & Jackson, 1986, Whitaker & Aitchison, 1985. Thus, even though neomycin and polylysine may share characteristics and properties, it is important to note that polylysine probably has several additional effects on cell function; indeed it may be of significance that polylysine easily internalizes into cells, while neomycin does not readily do so.…”
Section: Introductionmentioning
confidence: 99%